Attitude and purchasing decisions regarding genetically modified foods based on gender and education. (27th September 2011) - Heiman, Amir; Agmon, Ori; Fleisher, Racheli; Zilberman, David
Previous studies have found that gender affects perceptions and resistance to genetically modified food (GMF). Stronger aversion to innovations, lower technical interest, more concern with environment, and higher perceptions of environmental risk on the part of females relative to males have previously explained why females are less supportive of GMF. This study suggests a new explanation based on differences in economic benefits. Based on an empirical study, we show that, while males are more motivated by monetary incentives, females are less likely to prefer GMF if the incentive is price. They are more sensitive to moral and risk-reduction incentives. Education levels did not affect perceptions and preferences and thus cannot serve as explanatory variables to these gender differences. The insights gained may help policy makers in designing their communication campaigns aimed at increasing the adoption of genetically modified technology, which has the potential advantage of solving food scarcity and nutritional deficits.